Rapid Screening for EGFR Inhibitor in Rhei Radix et Rhizoma by HTRF Assay Coupled with HPLC Peak Fractionation - Fu, Yu; Xie, Zhishen; Zhao, Peng; Lv, Shuangshuang; Chen, Suiqing (Planta Medica, 2020)
In this paper, an HPLC peak fractionation approach combined with homogeneous time-resolved fluorescence analysis is proposed for screening epidermal growth factor receptor inhibitors from Rhei Radix et Rhizoma. With this approach, the amount of sample used for a single HPLC run is sufficient for performing a multiple assay due to the miniaturization ability of the homogeneous time-resolved fluorescence technology. This allows for improving the stability and repeatability of the activity assay for each fraction. From a total of 26 fractions collected from the Rhei Radix et Rhizoma extract, 13 fractions exhibit inhibitory activity against the epidermal growth factor receptor. The structures of activity compounds were determined by HPLC-LTQ-Orbitrap MS, revealing the presence of gallic acid, rhein, and emodin with IC50 values of 21.5, 5.29, and 10.2 µM, respectively. The ligand epidermal growth factor receptor interactions were explored by molecular docking simulations, and the inhibitory effects of the three compounds on A549 cell growth were tested in vitro by an MTT assay. This study demonstrates the suitability of the present screening method for drug discovery in natural products.
Keywords: Peak fractionation; HTRF; EGFR; Rheum palmatum; Polygonaceae